Analysis of Fiscal Independence, Fiscal Dependence, and Fiscal Effectiveness of Central Lombok Regency 2019-2023 - Wulandari, Resty; Manan, Abdul; Fatimah, Siti (Westscience Press, 2024)
This study aims to analyze